Safe Passage : Astronaut Care for Exploration Missions. - Ball, John; Evans, Charles H. (National Academies Press, 2001)
This report looks at issues surrounding astronaut health and safety for long duration space missions and makes recommendations regarding the infrastructure for a health system in space, the principles that should guide such a system to provide a standard of care for astronauts, and the nature of the clinical and health services research required before and during long-term missions for astronauts. Chapters cover risks to astronaut health, emergency and continuing care, behavioral health and performance, the ethics of space medicine, and planning an infrastructure for astronaut health care. Ball is chair of the Committee on Creating a Vision for Space Medicine During Travel Beyond Earth Orbit. Annotation copyrighted by Book News Inc., Portland, OR.